2017
DOI: 10.1093/geronb/gbx019
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Growth Mixture Modeling for Studying Resilience to Major Life Stressors in Adulthood and Old Age: Lessons for Class Size and Identification and Model Selection

Abstract: Our findings showcase that the assumptions typically underlying GMM are not tenable, influencing trajectory size and identification and most importantly, misinforming conceptual models of resilience. The discussion focuses on how GMM can be leveraged to effectively examine trajectories of adaptation following MLS and avenues for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 39 publications
(56 reference statements)
5
55
0
Order By: Relevance
“…More specifically, Diallo and colleagues (2016) found that assuming homogeneity of variance led to over-extraction of classes; data were simulated for one-class underlying the sample, and by applying the aforementioned assumption of homogeneity of variance lead to 4 classes being found in the data. Using empirical data, Infurna and Grimm (in press) further demonstrated the importance of the homogeneity of variance of assumption by showing that relaxing this assumption led to improved model fit and better identification of sub-groups in the data. In sum, results of this study confirm the critical need for researchers to allow for such variability; the failure to allow for these in assumptions applied at the outset can lead to misleading findings about the nature and sizes of resilient trajectories (Infurna & Grimm, in press; Infurna & Luthar, 2016; in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, Diallo and colleagues (2016) found that assuming homogeneity of variance led to over-extraction of classes; data were simulated for one-class underlying the sample, and by applying the aforementioned assumption of homogeneity of variance lead to 4 classes being found in the data. Using empirical data, Infurna and Grimm (in press) further demonstrated the importance of the homogeneity of variance of assumption by showing that relaxing this assumption led to improved model fit and better identification of sub-groups in the data. In sum, results of this study confirm the critical need for researchers to allow for such variability; the failure to allow for these in assumptions applied at the outset can lead to misleading findings about the nature and sizes of resilient trajectories (Infurna & Grimm, in press; Infurna & Luthar, 2016; in press).…”
Section: Discussionmentioning
confidence: 99%
“…For example, what is the importance of categorizing participants into the commonly found classes (e.g., resilient, recovery, growth, and chronic low) based on their trajectories over time (for discussion, see Infurna & Grimm, in press)? As shown in Figure 2, the distinctiveness between classes is mostly due to differences in levels in the outcome rather than on the trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this decision is often rooted in a desire to reduce the complexity of the estimation rather than for substantive reasons (Bauer & Curran, 2003;Enders & Tofighi, 2008;Gilthorope et al, 2014;Harring & Hodis, 2016, Infurna & Grimm, 2017Infurna & Luthar, 2016;van de Schoot, Sijbrandij, Winter, Depaoli, & Vermunt, 2017).…”
Section: Within-class Variationmentioning
confidence: 99%
“…Though commonly implemented in empirical settings (Infurna & Grimm, 2017), the approach of constraining variance terms across classes has been widely criticized in the methodological literature. The main reason being that the rationale behind this modeling decision is to aid estimation rather than because theory posits that each latent class actually has equal variance(s).…”
Section: Within-class Variationmentioning
confidence: 99%
See 1 more Smart Citation